The ecology of palm genomes: repeat‐associated genome size expansion is constrained by aridity. Issue 2 (7th July 2022) - Schley, Rowan J.; Pellicer, Jaume; Ge, Xue‐Jun; Barrett, Craig; Bellot, Sidonie; Guignard, Maïté S.; Novák, Petr; Suda, Jan; Fraser, Donald; Baker, William J.; Dodsworth, Steven; Macas, Jiří; et al.
Summary: Genome size varies 2400‐fold across plants, influencing their evolution through changes in cell size and cell division rates which impact plants' environmental stress tolerance. Repetitive element expansion explains much genome size diversity, and the processes structuring repeat 'communities' are analogous to those structuring ecological communities. However, which environmental stressors influence repeat community dynamics has not yet been examined from an ecological perspective. We measured genome size and leveraged climatic data for 91% of genera within the ecologically diverse palm family (Arecaceae). We then generated genomic repeat profiles for 141 palm species, and analysed repeats using phylogenetically informed linear models to explore relationships between repeat dynamics and environmental factors. We show that palm genome size and repeat 'community' composition are best explained by aridity. Specifically, Ty3‐gypsy and TIR elements were more abundant in palm species from wetter environments, which generally had larger genomes, suggesting amplification. By contrast, Ty1‐copia and LINE elements were more abundant in drier environments. Our results suggest that water stress inhibits repeat expansion through selection on upper genome size limits. However, elements that may associate with stress‐response genes (e.g. Ty1‐copia ) have amplified in arid‐adapted palm species. Overall, we provide novel evidence of climate influencing the assembly of repeat 'communities'.